ANALYSIS OF A DRINKING WATER DISTRIBUTION NETWORK USING EPANET 2.2 IN THE LOBUNTA HOUSING COMPLEX, BANJARWANGUNAN VILLAGE: ANALISIS JARINGAN DISTRIBUSI AIR BERSIH MENGGUNAKAN EPANET 2.2 DI PERUMAHAN LOBUNTA KELURAHAN BANJARWANGUNAN - Helenadya Greennov; Awliya Tribhuwana (Universitas Negeri Surabaya, 2026)
The clean water distribution network is a critical infrastructure for meeting the needs of the community. However, problems such as low water pressure, uneven distribution, and high water loss frequently occur in piping systems. This study aims to evaluate the performance of the clean water distribution network in the Lobunta Housing Complex, Banjarwangunan Village, using EPANET 2.2 software. The methodology employs quantitative descriptive analysis and hydraulic simulation based on pipeline network data, water demand, elevation, and customer usage patterns. The parameters analyzed include pressure, flow rate, flow velocity, and the level of water loss (Non-Revenue Water/NRW). The simulation results estimate that the network consists of 172 junctions with a total pipe length of approximately 9,988 meters. Water pressure ranges from 12.19 to 20.05 meters and meets the technical standards of Ministry of Public Works Regulation No. 18/PRT/M/2007. However, the maximum flow velocity of 0.27 m/s remains below the established minimum standard. Furthermore, the water loss rate of 40.75% indicates that the distribution system is not yet operating efficiently. Therefore, an evaluation and improvement of the network are necessary to enhance distribution efficiency and the quality of clean water service.